Determinan Pendeteksian Kecurangan Penyajian Laporan Keuangan : Studi Empiris pada Inspektorat Provinsi Sulawesi Selatan - Fera Firyal Thahir (Insan Cita Bongaya Research Journal, 2024)
This study aims to analyze the influence of understanding good governance and the expertise of internal auditors on the detection of fraud in the presentation of financial statements. at the South Sulawesi Provincial Inspectorate. Understanding good governance, and the expertise of internal auditors as independent variables and fraud detection as dependent variables. The population in this study is all auditors who work at the South Sulawesi Provincial Inspectorate. Sampling was carried out using the Nonprobality Sampling method, and the number of samples was 41 respondents. The collection method uses primary data obtained from the distribution of questionnaires. The data analysis technique used in this study is multiple regression analysis technique. The results of the study showed that the understanding of good governance had no effect and the expertise of internal auditors had an effect on the detection of fraud in the presentation of financial statements.